Analysis of history subject teaching modules in high school: A review based on the Merdeka Curriculum - Mulyani, Fini Fajri; Syahriani, Fadilla; Santos, Mariano Dos (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2024)
This research aims to analyze teaching modules that have been developed by history teachers in terms of the Merdeka Curriculum policy by paying attention to aspects of the completeness and systematics of teaching modules, and aspects of the content of teaching modules. The method used in this research uses descriptive qualitative methods. The data collection technique only uses documentation techniques in the form of teaching modules for history teachers at SMAN 1 Padang and SMAN 1 Ranah Pasisia. The data analysis technique uses techniques developed by Habermas, namely data reduction, data presentation, and verification or conclusion. The research results show that the teaching modules from both schools meet the Ministry of Education and Culture's curriculum standards and are by Ministry of Education and Culture Decree No. 008/H/KR/2022. Teachers at both schools succeeded in integrating historical thinking skills, historical awareness, and historical research into learning. However, there are differences in the development of practical historical skills, the local material included, and the development of summative assessments. This analysis shows variations in the approach, completeness, and presentation of material in history teaching modules in the two schools. Evaluation of teaching module components, skills development, the material contained, and formative and summative assessments are needed to improve the quality of history learning in both schools. The implications of this research show that there are variations in the approach, completeness, and presentation of materials in the history teaching modules in both schools.